2016
DOI: 10.3892/or.2016.4565
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3 inhibitor inhibits cell proliferation and induces apoptosis in human osteosarcoma cells

Abstract: Glycogen synthase kinase-3 (GSK-3) is a serine/threonine kinase that functions in numerous signaling pathways initiated by diverse stimuli. The functions of GSK-3 in cancer differ depending on cell type. In the present study, we examined the effects of a specific GSK-3 inhibitor on the regulation of osteosarcoma cell proliferation and apoptosis. Immunohistochemical analysis and real-time reverse transcription-polymerase chain reaction (RT-PCR) were performed to determine the expression pattern of GSK-3 in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The most pronounced and common hallmark property of cancer is persistent tumor cell survival with evasion of apoptosis and proliferation [179]. As shown in Table 1, GSK3β sustains tumor cell survival in many cancer types by exploiting various pro-survival pathways mediated by nuclear factor (NF)κ-B [48,[52][53][54][55]63,78,94,95,98,107,128,129,151,153], Hh/Gli [43], mammalian target of rapamycin (mTOR) [97,140] and signal transducers and activators of transcription (STAT)3 [27,68]. Additionally, GSK3β helps tolerate apoptotic stimuli induced by the tumor necrosis factor-related apoptosis inducing ligand (TRAIL) receptor-dependent synthetic lethal system [36,57,61,71,74,83,107].…”
Section: Gsk3β and Tumor Cell Survival Evasion Of Apoptosis And Prolmentioning
confidence: 99%
See 1 more Smart Citation
“…The most pronounced and common hallmark property of cancer is persistent tumor cell survival with evasion of apoptosis and proliferation [179]. As shown in Table 1, GSK3β sustains tumor cell survival in many cancer types by exploiting various pro-survival pathways mediated by nuclear factor (NF)κ-B [48,[52][53][54][55]63,78,94,95,98,107,128,129,151,153], Hh/Gli [43], mammalian target of rapamycin (mTOR) [97,140] and signal transducers and activators of transcription (STAT)3 [27,68]. Additionally, GSK3β helps tolerate apoptotic stimuli induced by the tumor necrosis factor-related apoptosis inducing ligand (TRAIL) receptor-dependent synthetic lethal system [36,57,61,71,74,83,107].…”
Section: Gsk3β and Tumor Cell Survival Evasion Of Apoptosis And Prolmentioning
confidence: 99%
“…Recently, our group and others reported a therapeutic effect of GSK3β inhibition against osteosarcoma [151][152][153][154], rhabdomyosarcoma [155,156], synovial sarcoma and fibrosarcoma [157]. These malignancies comprise the majority of sarcomas encountered in orthopedics for surgical removal.…”
Section: Gsk3β and Normal Tissue Damage Associated With Surgery For Cmentioning
confidence: 99%
“…Notably, GSK 3β inhibitor, SB216763, comparatively decreases the proliferation of GBM cells and induces apoptosis of GBM cells by halting DSB repair. Similarly, it has been revealed that GSK 3β inhibitor could block the NF-κB pathway and reduce the NF-κB-mediated transcription in osteosarcoma (OSA) ( 76 ).…”
Section: Role Of Gsk 3β In Tumorigenesismentioning
confidence: 99%
“…Using a number of toolkit inhibitors of GSK-3β, translational studies credentialed GSK-3β as a therapeutic target in multiple tumor types including pancreatic cancer (8, 9), chronic lymphocytic leukemia (10), colon (11), renal (12) and bladder (13) cancer. More recent studies have also shown that the inhibition of GSK-3β suppressed cancer cell viability in models of glioblastoma (1416), leukemia (1720), neuroblastoma (21, 22), osteosarcoma (23), melanoma (24), ovarian (25, 26), thyroid (27), prostate (2830), breast (3133) and lung cancer (34, 35). Thus, GSK-3β has emerged as a viable therapeutic target for the treatment of a broad spectrum of different cancer types.…”
Section: Introductionmentioning
confidence: 99%